Desempenho, parâmetros sanguíneos e fisiológicos de ovelhas morada nova suplementadas a pasto com duas fontes proteicas - Silva, Mirelio Ferreira da (2024)
The productive performance of grazing sheep supplemented with industrial detoxified castor bean meal as a protein source was evaluated. Two experiments were carried out, one in the city of Fortaleza/CE, with 29 white Morada Nova bitches weighing an average of 45 ± 8 kg grazing Tamani grass and Basilisk grass, and the other in Pentecoste/CE, with 26 red Morada Nova bitches weighing an average of 35 ± 6 kg grazing Tanzania grass. A completely randomized design was used, with plots subdivided by time, and the experimental diets consisted of two protein sources: soybean meal (SS) or industrially detoxified castor bean meal (IDFM). The sub-plots were the stages of the sows' produc- tive cycle (dry/empty; gestation; early lactation and late lactation), with 13 or 14 repeti- tions (sows) depending on the treatment. In the early and late lactation phases, the perfor- mance of the lambs was evaluated as an effect of maternal nutrition. In the physiological variables of the white and red sows, only the heart rate was higher in gestation compared to the other phases, there was no effect of the diets, or interaction between phases and diets. The performance of the white and red sows was not influenced by the diets or the interaction between phase and diet. In the dry/empty phase, the white sows had a lower average weight (42.89 kg), higher total weight gain (TWG; 5.04 kg), average daily gain (ADG; 0.048 kg) and body condition score (BCS; 3.570) compared to the other phases. Red sows had higher GPT in the dry/empty (4.190 kg) and gestation (4.536 kg) phases and lower ECC (3.034) and average weight (32.050 kg) in gestation. Lambs born to white dams fed FMID had higher GMD and GPT. The diet of the red sows did not influence the lambs' performance. There was an influence of diet on blood urea levels, with higher averages for white sows (40.51 mg/dl) and red sows (41.87 mg/dl) that consumed FS. Higher blood phosphatase (172.48 U/L) and bilirubin (0.40 mg/dl) values were observed in red sows supplemented with FS and gamma-glutamyl-transferase (GGT) in red sows fed FMID. Total protein, creatinine and glucose levels were higher at the start of lactation in both varieties. Albumin, triglycerides and phosphatase were higher in early lactation and in the dry/empty phase for red and white sows, respectively. The concentration of cholesterol and leukocytes was higher in the dry/empty phase only in the white variety. The levels of urea, hemoglobin, oxalacetic transaminase (TGO) and bilirubin were higher at the beginning of lactation in both varieties. GGT was influenced by the stage of early lactation, with a lower average only for red sows. The use of FMID as a protein source for long periods does not generate a cumulative intoxication effect in sheep, does not alter physiological variables and meets the nutritional requirements of grazing dams during the phases of the production cycle, and can fully replace soybean meal. Lambs from white and red dams supplemented with FMID did not have their performance compromised by the diet fed to the dams.